Hubungan Obesitas Dengan Kadar Gula Darah Pada Mahasiswa Fakultas Kedokteran Universitas Muslim Indonesia - Yaumil Khair; Asrini Safitri; Indah Lestari Daeng Kanang; Sho Latief; Rasfayanah (Universitas Muslim Indonesia, 2023)
Obesity is a global public health problem, contributing to increased morbidity and mortality. Obesity is a multifactorial disease that adversely affects many organ systems. The prevalence of obesity in Indonesia has shown an increasing trend, 10.5% since 2007, 14.8% in 2013, and 21.8% in 2018. This study aims to determine the relationship between obesity and elevated blood glucose levels among medical students of Muslim University of Indonesia in 2019. The type of study conducted was an observational analytical study with a cross-sectional research design. The total sampling method was used, and the population was the same as the sample, 49 people. Based on the Pearson correlation test, the obtained significance value is 0.252, this value > 0.05, which means there is no relationship between obesity and blood glucose level among medical students of Islamic Indonesian University in 2019. The correlation coefficient is 0.167, meaning that the closeness of the relationship between the obesity variable and blood glucose level at that time is 0.167 or falls under shallow criteria.